Supervisory Incentives in a Banking Union - Carletti, Elena (IMF Working Papers; Working Paper, 2016)
We explore the behavior of supervisors when a centralized agency has full power over all decisions regarding banks, but relies on local supervisors to collect the information necessary to act. This institutional design entails a principal-agent problem between the central and local supervisors if their objective functions differ. Information collection may be inferior to that under fully independent local supervisors or under centralized information collection. And this may increase risk-taking by regulated banks. Yet, a 'tougher' central supervisor may increase regulatory standards. Thus, the net effect of centralization on bank risk taking depends on the balance of these two effects.